A Preliminary Study to find the Pattern of Infectious Diseases in Buner - Muhammad Naeem, Fahad Ullah, Muhammad Zahid, Khalida Kousar, Fazal Akbar, Zahid Ullah Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Proper education of common men about the life threating infectious diseases in the surrounding is very much important in the modern therapeutic approaches. This study was carried out to find the most common devastating diseases in Buner region, the incidence and pattern of diseases were also determined. A total of 2354 hospital visited suspected patients were diagnosed for the presence of various infectious diseases in three main laboratories of District Buner (Riaz clinical laboratory, Azeem clinical laboratory and Bilal medical trust hospital laboratory). Out of total 2354 individuals 378 (16.05%) were positive for the infectious diseases. The major pathogenic disease in the studied area were Typhoid (salmonella typhi), H. pylori (helicobacter pylori), Malaria (Plasmodium), hepatitis C (hepatitis C virus) and hepatitis B (hepatitis B virus). Among the 378 patients screened for infectious diseases 243 (64.285%) were females and 135 (35.714%) were males. The incidence of each infections or diseases were maximum in the age group of 21-30 years old infected patients. The month wise distribution of each disease was different than the others. This study will attract the attention of government and non-government organizations towards the major health issues in Buner and would further encourage research work on these devastating diseases. The study will also uncover the involved disease factor and will help to control life threating diseases in future. Keywords: Infectious disease, Typhoid, H. pylori, Malaria